2017
DOI: 10.1504/pcfd.2017.081715
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic fracturing process by using a modified two-dimensional particle flow code - case study

Abstract: By using a modified PFC 2D model, the authors conducted a series of simulations to examine the influences of in-situ stress ratio, fluid injection rate, anisotropy of laminated rocks, and perforation parameters on hydraulic fracturing process. The simulations indicated that: 1) larger in-situ stress ratio will induce smaller breakdown pressures and faster propagation, and hydraulic fractures will extend along the direction of the maximum principal stress or approach to this preferred path; 2) smaller differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…As we know, faster fluid injection implied a higher strength similar to compressive tests of rock specimens applied with dynamic loads in the laboratory. Because stress in the solid skeleton induced by the injection borehole could not immediately adjust, higher fluid injection rate would lead to larger breakdown pressure in hydraulic fracturing [22]. What is more, when the injection rate reached to a large value (such as 5.0×10 -4 m 3 /s, shown in Fig.…”
Section: The Influence Of Fluid Injection Ratementioning
confidence: 98%
See 3 more Smart Citations
“…As we know, faster fluid injection implied a higher strength similar to compressive tests of rock specimens applied with dynamic loads in the laboratory. Because stress in the solid skeleton induced by the injection borehole could not immediately adjust, higher fluid injection rate would lead to larger breakdown pressure in hydraulic fracturing [22]. What is more, when the injection rate reached to a large value (such as 5.0×10 -4 m 3 /s, shown in Fig.…”
Section: The Influence Of Fluid Injection Ratementioning
confidence: 98%
“…The remaining microscopic parameters of BPM and SJM were the same as Table 1 and Table 2. With references of the previous research [21][22][23][24][25], the microscopic parameters in the fluid calculation were shown in Table 4. In order to verify the numerical model of hydraulic fracturing, hydraulic fracturing tests were carried out under different initial in-situ stresses.…”
Section: Establishment and Verification Of Hydraulic Fracturing Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, a large amount of research has been carried out to figure out the mechanism of hydraulic fracturing by means of experiments, simulations, and theoretical analysis. Various studies have shown that the main factors influencing hydraulic fracturing include external factors [5][6][7][8], such as in-situ stress, fluid viscosity and injection rate, and wellbore geometry, and internal factors [9][10][11][12][13], such as rock strength, natural fracture features, and rock anisotropy and heterogeneity.…”
Section: Introductionmentioning
confidence: 99%